2021
DOI: 10.1038/s41385-021-00419-1
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and commensal induction of IL-18 drive intestinal epithelial MHCII via IFNγ

Abstract: Major Histocompatibility Complex Class II (MHCII) is dynamically expressed on intestinal epithelial cells (IECs) throughout the intestine, but its regulation remains poorly understood. We observed that spontaneous upregulation of IEC MHCII in locally-bred Rag1 −/− mice correlated with serum Interleukin (IL)-18, was transferrable via cohousing to commercially-bred immunodeficient mice and could be inhibited by both IL-12 and IL-18 blockade. Overproduction of intestinal IL-18 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 56 publications
0
12
0
Order By: Relevance
“…At this time point, mice start to consume solid food and this leads to profound changes in microbiota composition initiating a robust immune response (Al Nabhani et al, 2019). While it is known that MHCII expression on IECs affects the severity of various immunopathologies (Jamwal et al ., 2020; Thelemann et al, 2014) and is dependent on intestinal microbiota (Van Der Kraak et al, 2021), very little is known about the role of MHCII + IECs in regard to time-dependent microbiota responses. Specifically, it is still unclear when exactly IECs start to express MHCII, what specific signals induce it, or whether it conveys any of the time-dependent microbiota-induced stimuli.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…At this time point, mice start to consume solid food and this leads to profound changes in microbiota composition initiating a robust immune response (Al Nabhani et al, 2019). While it is known that MHCII expression on IECs affects the severity of various immunopathologies (Jamwal et al ., 2020; Thelemann et al, 2014) and is dependent on intestinal microbiota (Van Der Kraak et al, 2021), very little is known about the role of MHCII + IECs in regard to time-dependent microbiota responses. Specifically, it is still unclear when exactly IECs start to express MHCII, what specific signals induce it, or whether it conveys any of the time-dependent microbiota-induced stimuli.…”
Section: Resultsmentioning
confidence: 99%
“…While SFB are best known for their induction of a T H 17 response (Gaboriau-Routhiau et al ., 2009; Ivanov et al ., 2009), it was also reported that SFB can increase IFNγ production in the gut (Gaboriau-Routhiau et al ., 2009). The latter finding may be crucial since IFNγ is a well-documented modulator of MHCII expression (Koyama et al ., 2019; Thelemann et al ., 2014; Van Der Kraak et al ., 2021). Therefore, we next measured the induction of IL-17a and IFNγ cytokines in the SI-LP after SFB colonization of JAX mice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have linked the requirement for the microbiota in regulating IEC-intrinsic MHCII expression (4448). Many of these studies have focused on how immune cells can induce epithelial MHCII through IFNγ signaling (44, 71, 72). In addition, disruption to canonical pattern recognition pathways leads to loss of intestinal barrier integrity and increased inflammation (73–75), and the toll-like receptor signaling adaptors MyD88/TRAF have been shown to induce epithelial MHCII expression, particularly in the small intestine (44).…”
Section: Discussionmentioning
confidence: 99%